Solution-assisted Energy-savvy Synthesis of High-voltage Na2M2(SO4)3 (M = 3d metals) Alluaudite Family of Sodium Insertion Materials. (2018) - Dwibedi, D.; Barpanda, P.
Abstract: The benchmarking of Fe 3+ /Fe 2+ redox potential at 3.8 V (versus Na) in alluaudite-type Na2 Fe2 (SO4 )3, along with fast rate kinetics and excellent cycling stability (Nat. Commun., 5, 4358, 2014) has opened up new era of research in Na-ion research. Further insight to the reported material show synthesis is a careful solid-state method involving (a) formation of anhydrous FeSO4 from commercial FeSO4. 7H2 O, (b) prolonged milling and (c) longer annealing (350°C, 24 h). Journey of such materials from laboratory to industry warrants economic, sustainable and scalable synthesis. Here, we report novel solution assisted- Ionothermal, aqueous spray-drying and pechini synthesis of Na2 Fe2 (SO4 )3, [M = 3d metals] alluaudite cathodes. It will approach (i) salient feature of synthesis, (ii) structure/polymorphism, (iii) magnetic properties and (iv) electrochemical properties of Na2 Fe2 (SO4 )3 cathode materials.